2011
DOI: 10.1080/15374416.2011.581619
|View full text |Cite
|
Sign up to set email alerts
|

An Effectiveness Study of a Culturally Enriched School-Based CBT Anxiety Prevention Program

Abstract: Anxiety disorders are prevalent in the school-aged population and are present across cultural groups. Scant research exists on culturally relevant prevention and intervention programs for mental health problems in the Aboriginal populations. An established cognitive behavioral program, FRIENDS for Life, was enriched to include content that was culturally relevant to Aboriginal students. Students (N = 533), including 192 students of Aboriginal background, participated in the cluster randomized control study. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 38 publications
5
48
0
1
Order By: Relevance
“…As noted, these null findings were likely related to a lack of a clearly delineated control group and longer follow-up, with the latter possibly allowing more time to practice and develop the anxiety coping skills taught. Similar null findings were reported by Miller et al (2011) who randomized 533 children (including many Aboriginal children residing in Canada) to the intervention (FRIENDS culturally adapted) ( n = 269) or a waitlist ( n = 264). Findings showed that no statistically significant reductions in anxiety levels could be attributed to the intervention.…”
supporting
confidence: 69%
See 2 more Smart Citations
“…As noted, these null findings were likely related to a lack of a clearly delineated control group and longer follow-up, with the latter possibly allowing more time to practice and develop the anxiety coping skills taught. Similar null findings were reported by Miller et al (2011) who randomized 533 children (including many Aboriginal children residing in Canada) to the intervention (FRIENDS culturally adapted) ( n = 269) or a waitlist ( n = 264). Findings showed that no statistically significant reductions in anxiety levels could be attributed to the intervention.…”
supporting
confidence: 69%
“…To secure culturally responsive child anxiety interventions, some degree of cultural adaptation seems necessary based on findings from Cooley et al (2004), Cooley-Strickland et al (2011), Huey and colleagues (2006, 2011), Griner and Smith (2006), Miller et al (2011) and Pina et al (2003; 2012). Research to date offers some sense about what might (or not) work.…”
Section: Concluding Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further factor which is emerging as important in implementation studies is the compatibility of prevention programmes with the school culture and competing priorities. How they practically fit within a complex and full timetable have been identified as major obstacles that can impede effective delivery 10 11 14 16…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an implementation trial in Canada 63 school staff were trained to deliver FRIENDS to 533 students aged 10–12 attending 15 schools 14. Although treatment fidelity was high and children rated their understanding of the programme as good FRIENDS did not have a significant effect on anxiety for either native or aboriginal students at 6 months.…”
Section: Anxiety Preventionmentioning
confidence: 99%